Adsorption of volatile organic compounds over MIL-125-NH2. (1st November 2018) - Kim, Bomi; Lee, Yu-Ri; Kim, Hee-Young; Ahn, Wha-Seung
Graphical abstract: Adsorption of volatile organic compounds (VOCs) over MIL-125-NH2 was investigated by measuring their adsorption isotherms. Significant amounts of the VOCs were adsorbed, and their adsorption capacities followed the order of increasing polarity. Abstract: Volatile organic compounds (VOCs) cause environmental and health problems by forming photochemistry smog, and development of an effective adsorbent for their removal is important. In this work, adsorption of a series of selected VOCs over an amine-functionalized metal organic framework, MIL-125-NH2, was investigated by measuring their adsorption isotherms at three different temperatures. Significant amounts of the VOCs were adsorbed, and their adsorption capacities increased with the increasing order of polarity ( p -xylene < toluene < benzene < acetone < isopropanol). In addition, formaldehyde breakthrough capacities were measured and MIL-125-NH2, exhibited a clearly superior performance to other MOFs, probably because of the synergistic effects provided by the amine groups that strongly interacting with the formaldehyde and the small micropores in MIL-125-NH2 .